Konseptualisasi Pemenuhan Hak Asasi Manusia Generasi Mendatang Atas Lingkungan Hidup - Muhammad Khatami; Yuda Mustajab (Forschungsforum Law Journal, 2026)
This research aims to conceptualize the human rights of future generations over the environment. This article begins its discussion with the issue of the incomplete availability of laws to guarantee the human rights of future generations over the environment, especially when this is seen in terms of comparison with several other countries. For this reason, this article questions about the legal guarantee of the fulfillment of human rights for future generations and the design of its fulfillment. Using normative legal research methods, this article has formulated the answer. According to its findings, this article views that the human rights of future generations to the environment are an integral part of the human rights regime itself with the status of collective rights in the building of the third generation of human rights. The principle is that the nature of human rights itself is continuously connected to each generation of human life (continuity). Its legal guarantee is based on the principle of intergenerational equity which gives the current generation the responsibility to protect and respect it. At the same time, it is also up to the state to realize its fulfillment by protecting, to respect, and to fulfil through every implementation of state functions carried out by each branch of state power itself, both inside and outside the territory of the country itself (cross-territorial responsibility).